Comparison of the Bending Behavior of Cylindrically Shaped Lattice Specimens with Radially and Orthogonally Arranged Cells Made of ABS - Monkova, Katarina; Monka, Peter Pavol; Vodilka, Adrián (Polymers, 2024)
The article deals with the comparison of the bending behavior of cylindrical lattice samples with radially and orthogonally arranged cells made of ABS material. The structures were designed in PTC Creo Parametric 8 software, while four types of lattice structures were evaluated: Rhombus, Cuboidal BCC, Octagon, and Starry, in three material volume fractions: 44, 57, and 70%, together with tubular and rod-shaped samples. The Fused Filament Fabrication (FFF) technique was chosen for the production of ABS plastic samples. Based on the bending tests, the dependences of the force on the deflection were recorded and the obtained data were statistically processed to identify outliers using the Grubbs test. The maximum stresses were calculated and the dependences of the stresses on the volume fractions were plotted. Along with energy absorption, ductility indices were also specified. Although the Rhombus structure appears to be the best based on the ductility indices obtained, on the other hand, the structure showed the lowest values of bending stresses (in the range from 10.6 to 12.6 MPa for volume fractions ranging from 44 to 70%, respectively). Therefore, from a synergic point of view of both factors, stress and ductility, the Starry structure exhibits the best flexural properties among those investigated.
Keywords: cell arrangement; ductility index; bending behavior; lattice structure; ABS plastics